Sediment and incubation characteristics from the southeastern North Sea during Heincke cruise HE582 in August and September 2021 - Minutolo, Fabrizio (PANGAEA, 2025)
This dataset comprises biogeochemical and sedimentological measurements from surface sediments collected in the southern North Sea during the HEINCKE HE582 campaign in August and September 2021. Surface sediment of the southern North Sea was incubated in flow through reactors (~24h) to quantify benthic oxygen consumption, net silicate turnover, ammonium and nitrate turnover (net and gross rates). Net turnover was derived from concentration gradients between inflow and outflow water under controlled laboratory conditions. Gross turnover was derived using 15NH4 and 15NO3 tracer. Following the incubations, the surface sediment was analyzed for sediment characteristics, including phaeophytin-a, chlorophyll-a, grain size, mud content, TOC and carbohydrates. For a more detailed methodological description please refer to Minutolo et al. (2024).
Keywords: benthic nutrient turnover; flow-through measurement; incubation; sediment biogeochemistry; Southern North Sea